Diverse manifestations and management options in Klippel-Trenaunay syndrome: A single centre 10-year experience. Issue 4 (September 2013) - Sreekar, Harinatha; Dawre, Sandeep; Petkar, Kiran S.; Shetty, Rahul B.; Lamba, Shashank; Naik, Sukriya; Gupta, Ashish K.
Abstract Klippel-Trenaunay syndrome is a well-known conglomeration of capillary malformations, bony or soft tissue hypertrophy, and abnormal deep or superficial veins. Although it generally presents with grossly enlarged limbs, it can present with more serious features like haematuria, haematochezia, and seizures. This retrospective study included patients admitted with the diagnosis of Klippel-Trenaunay syndrome in this institute from 2001–2010. The patients' demographic data, clinical features, associated findings, and treatments given were tabulated. A total of 19 patients were included in the study. Two patients presented with haematocezia and had to undergo bowel resection. Five presented with bleeding and ulceration. Debulking surgery was done in three of them. Patients also presented with abdominal distension, jaundice, seizures, and haematuria. Although the common presentation of varicose veins was treated with sclerotherapy, the treatment was tailored to each patient. Klippel-Trenaunay syndrome is a multifaceted disorder which can manifest in a number of different ways. These features may be missed by an unwary plastic surgeon treating them only for the limb hypertrophy.